2014
DOI: 10.1007/s10620-014-3157-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment of Constipation-Predominant Irritable Bowel Syndrome

Abstract: Rifaximin plus neomycin is superior to neomycin alone in improving multiple C-IBS symptoms. This effect is predicted by a reduction in breath methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 16 publications
5
75
0
6
Order By: Relevance
“…Rifaximin received regulatory approval for the treatment of IBS-D in May 2015; several studies indicated a favorable efficacy and safety profile for rifaximin in IBS-D (Table 3) [Di Stefano et al 2011;Pimentel et al 2006Pimentel et al , 2011Pimentel et al , 2014. The identically designed, randomized, placebo-controlled, phase III TARGET 1 and 2 studies examined the safety and efficacy of rifaximin 550 mg 3 times daily for 2 weeks in patients with IBS-D [Pimentel et al 2011].…”
Section: Targeting Gut Microbiotamentioning
confidence: 99%
“…Rifaximin received regulatory approval for the treatment of IBS-D in May 2015; several studies indicated a favorable efficacy and safety profile for rifaximin in IBS-D (Table 3) [Di Stefano et al 2011;Pimentel et al 2006Pimentel et al , 2011Pimentel et al , 2014. The identically designed, randomized, placebo-controlled, phase III TARGET 1 and 2 studies examined the safety and efficacy of rifaximin 550 mg 3 times daily for 2 weeks in patients with IBS-D [Pimentel et al 2011].…”
Section: Targeting Gut Microbiotamentioning
confidence: 99%
“…It prevents pathogens from adhering to the bowel mucosa and from invading epithelial cells by binding microbial RNA-polymerase subunit β, thus inhibiting transcription and the synthesis of ribonucleis acid (RNA) (101).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Rifaximin seems to reduce distension, flatulence and abdominal pain in patients with IBS without constipation, according to the relevant studies (90,(101)(102)(103). One study suggests its potential role for patients with IBS-C (104).…”
Section: Efficacymentioning
confidence: 99%
“…Since eradication of small intestine bacterial overgrowth was shown to reduce symptoms of IBS, 43 double-blind, randomized, placebo-controlled studies using these antibiotics have been conducted (Table 3). 28,[44][45][46] …”
Section: -mentioning
confidence: 99%